Analysis of Latin America's corporations as a rational response to the economic environment present in the region. Part III. Quantifying Latin American firms' exposure to external factors - Sergio A. Pernice; Mariano Fernández; María A. Alegre (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
This is the last of a series of three working papers analyzing the basic characteristics of the economic environment in which Latin American firms operate and the optimal design of incentive programs compatible with such environment. Executive pay-for-performance compensation schemes are usually based on stock returns. However, stock returns change in response to forces beyond management control (e.g., market crushes). The economic environment in which Latin American firms operate is highly unstable, which means that this is a very important limitation for Latin American firms. In the present paper, we present a procedure to decompose variability in stock returns in order to identify and measure components that respond to external factors beyond management control. For this, we have created indices that capture statistically the external influences that affect stock returns. We show how such indices can be used to construct a risk profile that allows management to know to what extent observed outcomes depend on external factors, versus their own actions. In addition, these indices can be used as a basis to develop indexed options: financial instruments designed to factor out the effects of external risks, making it possible for executives to be evaluated only on the basis of the value they generate. We show that these indices can be developed out of purely local information, but that the solutions tend to be moderately unstable, which implies that compensation instruments developed with this methodology should be of relatively short maturity.
Keywords: 330